Prevalence of Complications Associated With Hepatitis A Infection Among Children - Qayyum, Faiza; Haider, Nighat; Ambreen, Sara; Farooq, Ana; Ejaz, Sana; Zahid, Tehmina (Biological and Clinical Sciences Research Journal, 2025)
Hepatitis A virus (HAV) is a common cause of acute viral hepatitis in children, particularly in developing countries. While it is typically self-limiting, complications may arise and contribute to significant morbidity. Objectives: To determine the frequency of complications of hepatitis A in children infected with hepatitis A virus. Method: This cross sectional study conducted at Pediatrics department of Pakistan Institute of Medical Sciences, Islamabad, Pakistan from March-2022 to March-2024. In this study, a total of 140 patients with hepatitis A were included. Demographic data and clinical information of the participants including age, gender and weight was collected. Patients were assessed carefully and presence of any complication related to viral hepatitis A were documented. Data was stratified based on confounding variables and post-stratification comparison analysis was performed using Chi-square test while keeping the p-value of ≤ 0.05 as statistically significant. Software used for analysis was Statistical Package for Social Sciences version 20. Results: Median age was 7.00 (5.00) years. There were 86 (61.40%) male and 54 (38.60%) female patients. Frequency of patients who had viral hepatitis due to HAV and developed complications was 78 (55.70%). Most common complications observed were splenomegaly, low platelet count and pancytopenia affecting 12 (15.38%) patients each followed by ascites and dilated common bile duct (CBD) occurring in 10 (12.82%) each, diffuse cutaneous rash in 9 (11.54%) patients, hepatic encephalopathy (HE) occurring in 7 (8.97%) patients and fulminant hepatic failure in 6 (7.69%) patients. Conclusion: In patients with HAV related viral hepatitis, complications occurred in 55.70% patients.